Analisis Abnormal Return Saham Sebelum dan Sesudah Pengumuman Resmi Pemindahan Ibu Kota Indonesia (Saham yang Terdapat di JII) - Bunga Thuba Sembilan (MUSLIMPRENEUR : Jurnal Ekonomi dan Kajian Keislaman, 2021)
The announcement made by President Jokowi on August 26, 2019 to the National media related to the transfer of the Capital City of Jakarta to Kalimantan have an indication that there would be information that would affect the level of future returns on company shares. The existence of this issue caused turmoil in issuers of shares, several newspapers stated that there were shares in various affected sectors. The purpose of this study was to determine whether there was a turmoil that occurred in the information that was in the announcement of the transfer of the capital. The research method used in the form of event study. The results of this study are that there is a slight positive reaction to the stocks arising from the information related to the announcement of transfer planning, especially the impact on infrastructure and property companies listed on the JII index